Vasile Alecsandri. 22 august 1890 (Confluenţe Bibliologice, 2019)
In the article the author reports about the death of the writer Vasile Alecsandri, in Mircesti, after a serious illness. There have been hundreds of condolence telegrams from all classes of society. The telegrams of Queen Elizabeth, Princess Elena Cuza, Theodor Rosetti, I. C. Bratianu, G. Cantacuzino, etc. are recorded.Many speeches have been spoken. After the talks ended, students at the University of Bucharest took the coﬃn on their shoulders and, in the sound of marching, they took him to the grave. Among the wreaths could be read on the ribbons: Carmen Silva, Council of Ministers, Romanian Commune, Romanian Athenaeum, Romanian Academy, Galati Town, Sturdza Family, Vasile Alecsandri High School in Galati, Bucharest Conservatory, Junimea Society, Iasi City etc.
Keywords: Vasile Alecsandri (1821 - 1890); Romanian writers